Hybrid Active Power Filter for Power Quality Improvement (International Journal of Innovative Research in Computer Science & Technology, 2022)
A Deadbeat current controller for an LC coupling hybrid active power filter is proposed, which can  track with the reference compensation current with low  steady- state error and fast dynamic response. Moreover, it  can lead Hybrid Active power Filter to be operating at a fixed  switching frequency with low output current ripples, thus  reducing the size of the filtering circuit. The stability issue  and parameter design of the proposed deadbeat current  controller are analyzed and discussed. Finally, the  compensating performance of the deadbeat current controller  for the Hybrid Active Power Filter (LC-HAPF) is verified by  simulation compared with the conventional hysteresis  bandwidth modulation control, the proportional-integral (PI)  control, and the proportional multi-resonant control for the  LC-HAPF, which shows its effectiveness and superior  compensating performances.
Keywords: Power Filter; Power Quality; LC-HAPF; PMR